2008
DOI: 10.1115/1.2472417
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Heat Transfer Measurements on the Tip Wall of a Ribbed Channel Using a Novel Heat Flux Sensor—Part II: Heat Transfer Results

Abstract: Measurements using a novel heat flux sensor were performed in an internal ribbed channel representing the internal cooling passages of a gas turbine blade. These measurements allowed for the characterization of heat transfer turbulence levels and unsteadiness not previously available for internal cooling channels. In the study of heat transfer, often the fluctuations can be equally as important as the mean values for understanding the heat loads in a system. In this study, comparisons are made between the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…When light/heat is applied to the surface of the film, a temperature difference is generated along the thickness direction and a voltage signal is obtained. In the same year, Jenkins et al and Zhang et al compared the heat flux sensitivity performance of the YBa 2 Cu 3 O 7-δ , LaCaMnO 3 , LaPbMnO 3 , and LaSrCoO 3 material systems [24,25]. They also compared the transverse thermoelectric properties of YBa 2 Cu 3 O 7-δ films of different thicknesses, and found that at a thickness of 700 nm, the sensitivity was 6.9 µV/(kW•m 2 ) with a response time of less than 0.3 µs and a response frequency of 700 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…When light/heat is applied to the surface of the film, a temperature difference is generated along the thickness direction and a voltage signal is obtained. In the same year, Jenkins et al and Zhang et al compared the heat flux sensitivity performance of the YBa 2 Cu 3 O 7-δ , LaCaMnO 3 , LaPbMnO 3 , and LaSrCoO 3 material systems [24,25]. They also compared the transverse thermoelectric properties of YBa 2 Cu 3 O 7-δ films of different thicknesses, and found that at a thickness of 700 nm, the sensitivity was 6.9 µV/(kW•m 2 ) with a response time of less than 0.3 µs and a response frequency of 700 kHz.…”
Section: Introductionmentioning
confidence: 99%